Selected aspects of multicriteria analysis in the design of bypass roads - Żabicki, Piotr; Gardziejczyk, Władysław (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The multicriteria analysis is a method of supporting the decision process in a situation where there are many road alignment variants analyzed. The paper presents two examples of choosing the most beneficial variant for bypassing a town, located in the course of regional roads. The analysis was conducted basing on normalization methods by Van Delft and Nijkamp, Weitendorf, Peldschus and the weight of the considered criteria. The considered criteria describing the analyzed variants are usually expressed in different units. The use of normalization is necessary to achieve the comparability of the criteria.